Effect of Sago Starch Concentration on Characteristic of Sago Glucose Syrup - Rissa Megavitry; Amran Laga; Adiansyah Syarifuddin (Food ScienTech Journal, 2022)
Opportunity to use sago as a basic ingredient for syrup glucose is very large because of the high carbohydrate content reached 75.88% - 85.08%. Sago starch contains 27% amylose and 73% amylopectin. This study aims to determine the effect of sago starch substrate concentration on reducing sugar, total dissolved solids, dextrose equivalent, and sweetness level from the glucose syrup produced. This research was conducted in 3 stages, namely gelatinization, liquefaction, and saccharification. The use of sago substrate concentrations were 25%, 30%, and 35%. The use of amylase enzyme is 0.1% dry weight and glucoamylase enzyme is 0.008 g/g dry weight. This study used a completely randomized design with a factorial pattern with two replications and data analysis using Duncan test. The use of α-amylase and glucoamylase enzymes in the manufacture of glucose syrup from sago starch affects the glucose syrup produced. The best result is obtained from 30% substrate concentration with reducing sugar value is 186.07 g/L, total dissolved solid is 36.13%, dextrose equivalent value is 62.02%, and sweetness level value is 33.92 ºbrix.